A etnicidade do imigrante italiano nos periódicos na cidade de São Paulo 1870-1919 - Gonçalves, Rino Gabriel Siqueira (2019)
This work analyzes the ethnicity of the Italian immigrant and the way it is established in the city of São Paulo in the late nineteenth and early twentieth centuries, observing how the periodicals were part of the construction of Italianity. With research and analysis of some periodicals of the Italian colony and of the society of São Paulo, it was possible to find the constitutive language that leads to social and cultural practice that assimilations, tensions and cultural hybridism socialized the Italian colony in a city that grew rapidly. The relation of the periodicals with the readership has as its core the very historicity of the periodicals. In the case of the Italian newspapers I cite methodologically as fundamental the study beyond the newspaper as a source, considering that the periodicals are an active part of the history and have their historicity, being relevant the study regarding the origin of the periodicals, the life and participation of its owners and editors in the host society. The editorial and graphic designs beyond the ads in the chosen journals provided favorable conditions for producing this dissertation. Newspapers such as Fanfulla, La Barricata and Germinal were used in this work, other titles were used as illustration and complementary examples as the case of the Correio Paulistano and the State of São Paulo, because between the press of the time even the said national had interaction both friendly and rivalry between them. The constitution of the periodicals, their language, images and advertisements refer to the daily life of São Paulo and the insertion of a large number of Italian immigrants. The city of São Paulo and the "Italian-Paulistano" are simultaneously constituted in daily experiences or at historical moments such as the Question of the Italian Protocols (1896) and the General Strike of 1917. Places and habits are also indicated in the periodicals in order to contribute to the notion of how Italian was abstract in face of the multiplicity of immigrants from newly unified Italy. Reflecting on the questioning of a genuinely Italian ethnicity, and in the relations between the Italians themselves and the Paulistas